1983
DOI: 10.1038/jcbfm.1983.13
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH in the Brain following Transient Ischemia

Abstract: Summary:The objective of the present study was to discover whether or not intracellular alkalosis develops in the brain in the recovery period following transient ischemia, Forebrain ischemia of IS-min duration was in duced by four-vessel occlusion in rats, with recovery periods of IS, 60, and 180 min. Intracellular pH was derived both by the HC03--H2C03 method and from the creatine kinase equilibrium. The ischemia was associated with energy failure and marked accumulation of lactic acid in the cerebral cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 26 publications
8
50
0
Order By: Relevance
“…Moreover, this elevated NHE1 activity increased pH i to 7.38 after 60 min REOX from a basal level of 7.05. It has been reported that pH i is reduced in brain during transient ischemia and shifts in the alkaline direction during 60 min recovery and returns to normal levels at 3 h recovery (27). Activation of NHEs is thought to be one of the main mechanisms of alkalinization during reperfusion, which is consistent with our findings.…”
Section: Nhe1 Activity Is Stimulated In Cortical Neurons Aftersupporting
confidence: 82%
“…Moreover, this elevated NHE1 activity increased pH i to 7.38 after 60 min REOX from a basal level of 7.05. It has been reported that pH i is reduced in brain during transient ischemia and shifts in the alkaline direction during 60 min recovery and returns to normal levels at 3 h recovery (27). Activation of NHEs is thought to be one of the main mechanisms of alkalinization during reperfusion, which is consistent with our findings.…”
Section: Nhe1 Activity Is Stimulated In Cortical Neurons Aftersupporting
confidence: 82%
“…Since the values agreed well with the results obtained in four control animals in a concur rent study (Mabe et al, 1983), the values were pooled with these to give a group of six animals.…”
Section: Experimental Groupssupporting
confidence: 61%
“…Thus, phosphorylated polyUb can be either recruited or generated onsite. Upon oxidative stress, neurodegeneration, and aging, Ub phosphorylation level drastically increases (4,8,31), whereas mitophagy, apoptosis, ischemia, inflammation, aging, and many pathophysiological conditions are all associated with changes in cellular pH (32)(33)(34)(35). Altogether, it is likely that certain functions of pUb are only turned on in response to changes in both Ub phosphorylation level and environmental pH.…”
Section: Discussionmentioning
confidence: 99%